Gestión de talento humano del Supermercado Escobar Maliza Sucomesco S.A. del cantón Vinces periodo 2021. - Vera Onofre, Diana Paola (2022)
This Case Study was carried out at the Escobar Maliza Sucomesco S.A. Supermarket. of the Vínces Canton, whose purpose is to analyze the Management of Human Talent to improve the administrative functions and the performance of the collaborators, enhancing competitiveness in the market. The objective of this work is to offer knowledge about the human talent management processes so that they contribute to the improvement of its operation, as well as the importance of offering collaborators the necessary tools and knowledge through training and training programs so tata this develop and foster their skills according to what the company needs, being a very important factor to provide customers with a quality service at the Escobar Maliza Sucomesco S.A. Supermarket. To obtain information in this work, surveys and interviews were carried out to facilitate the timely solution of the problem under study.